Effectiveness of the Thinking Skills Development Program (Based on Brookfield’s Model) on Students’ Critical Thinking, Academic Resilience, and Academic Achievement - Shahab Afraz; Mansoureh Hajhosseini (پژوهش‌های کاربردی روانشناختی, 2021)
The purpose of the present study is to evaluate the effectiveness of thinking skills development program (based on Brookfield's model) on academic achievement, academic resilience and critical thinking The method of the study is a quasi-experimental study with pretest-posttest with a control group and was applied based on the purpose. The statistical population of the study consists of male high school students of Alborz Province of the 2018-2019 academic year who participated in one of the nationally validated pilot tests for the college entrance examination. The sample consists of thirty male high school students at one of the high schools in Karaj who were randomly assigned to an experimental group and a control group. The measures used in the study included: examinations test scores, Samuels’ Academic Resilience Inventory (ARI) and Ricketts Critical Thinking Disposition Inventory (CTDI). The program was conducted in 8 sessions of 90 minutes group training for the experimental group while the control group received no training. Multivariate analysis of covariance (MANCOVA) was used to evaluate the effectiveness of the program using the software IBM SPSS (version 23). The results show that implementing the Thinking Skills Development Program for studensts improved critical thinking (in three components: innovativeness, cognitive maturity, and engagement), academic achievement, and academic resilience (in two components: problem-oriented-positive and future-oriented). Communication skills were not statistically significantly different) among high school students. The results of the study confirm that it may be useful to include the program in the curriculum for high school students who fail the pilot tests for college entrance exams.